2000
DOI: 10.1029/1999ja900359
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the mass distribution of interstellar dust grains in the solar system from in situ measurements

Abstract: Abstract. The in situ detection of interstellar dust grains in the solar system by the dust instruments on-board the Ulysses and Galileo spacecraft as well as the recent measurements of hyperbolic radar meteors give information on the properties of the interstellar solid particle population in the solar vicinity. Especially the distribution of grain masses is indicative of growth and destruction mechanisms that govern the grain evolution in the interstellar medium. The mass of an impacting dust grain is derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
203
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(212 citation statements)
references
References 23 publications
8
203
1
Order By: Relevance
“…However, the abundance of even larger grains is not well determined. Studies of impacts of interstellar dust grains in the solar system (Landgraf et al 2000), of primitive, chondritic meteorites (Scott & Krot 2005) and the samples returned from comet 81P/Wild 2 by the Stardust mission (Brownlee et al 2006) showed larger dust grains, up to a size of ∼ 10µm. Assuming that these particles are the remains of the initial protoplanetary dust population, we can assume grain sizes not entirely different from the ones used in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abundance of even larger grains is not well determined. Studies of impacts of interstellar dust grains in the solar system (Landgraf et al 2000), of primitive, chondritic meteorites (Scott & Krot 2005) and the samples returned from comet 81P/Wild 2 by the Stardust mission (Brownlee et al 2006) showed larger dust grains, up to a size of ∼ 10µm. Assuming that these particles are the remains of the initial protoplanetary dust population, we can assume grain sizes not entirely different from the ones used in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Altobelli et al (2006); (2) Grün et al (1994); (3) Baguhl et al (1996); (4) Landgraf et al (2000); (5) Krüger et al (2007); (6) Baguhl et al (1996), (7) Altobelli et al (2005); (8) Altobelli et al (2003); (9) Krüger et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…These facts suggest that the detected grains are part of the interstellar dust population of the local interstellar cloud. An unexpected characteristic of the in situ-detected interstellar grains is that their inferred size distribution extends well beyond the maximum sizes usually adopted for interstellar grains (Landgraf et al 2000). It must be noted that the dust detectors are able to record the mass, speed, and direction of incoming grains with radii above 0.05 mm, where the grain radii are inferred by assuming spherical shapes and a bulk density of 2.5 g cm Ϫ3 for the particles.…”
Section: Introductionmentioning
confidence: 99%